Molecular characterization of Orientia tsutsugamushi causing scrub typhus among febrile patients in north-central Bangladesh - M.M. Al Amin; S.K. Paul; M.S. Aung; A. Paul; M.A. Aziz; N.A. Khan; A.K.M.F. Haque; F. Ahamed; A. Melan; S.R. Sarker; M.A. Hossain; S. Ahmed; et al. (New Microbes and New Infections, 2019)
Scrub typhus is a mite-borne rickettsial disease caused by Orientia tsutsugamushi, which is endemic in Asia Pacific region. In this study, infection rate and molecular epidemiologic traits of O. tsutsugamushi was investigated in Mymensingh, located in north-central Bangladesh. Among the blood samples from 453 febrile patients who visited Mymensingh medical college hospital in 2018, the 47 kDa protein gene of O. tsutsugamushi was detected in 78 samples (17.2%) by nested PCR. Phylogenetic analysis of the O. tsutsugamushi 56 kDa protein gene (18 samples) revealed a predominance of Karp-related genotype (89%), while the remaining belonged to Gilliam genotype. Samples of the Karp-related genotype mostly clustered with those of China, Taiwan, Thailand and India, etc., in emergent subgroups clades 2 and 4, which were distinct from clade 1, including prototype Karp strains. Among the 18 samples, three variable domains (VD) of 56 kDa type-specific antigen had different types of sequence diversity; VDI contained two or three repeats of eight amino acid units, while VDII and VDIII had amino acid substitution, deletion or insertion. The present study documented a potentially high prevalence of genetically diverse O. tsutsugamushi in north-central Bangladesh. Keywords: 56 kDa type-specific antigen, Bangladesh, Orientia tsutsugamushi, scrub typhus, Karp-related genotype